Methods for the isolation and analysis of Aβ from postmortem brain - Hong, Wei; Liu, Wen; Desousa, Alexandra O.; Young-Pearse, Tracy; Walsh, Dominic M. (Frontiers in Neuroscience, 2023)
Amyloid β-protein (Aβ) plays an initiating role in Alzheimer’s disease (AD), but only a small number of groups have studied Aβ extracted from human brain. Most prior studies have utilized synthetic Aβ peptides, but the relevance of these test tube experiments to the conditions that prevail in AD is uncertain. Here, we describe three distinct methods for isolating Aβ from cortical tissue. Each method allows the study of different ranges of species thus enabling the examination of different questions. The first method allows the isolation of readily diffusible Aβ with a relatively high specific activity. The second enables the isolation of readily solubilized forms of Aβ the majority of which are inactive. The third details the isolation of true Aβ dimers which have disease related activity. We also describe a bioassay to study of the effects of Aβ on the neuritic integrity of iPSC-derived human neurons. The combined use of this bioassay and the described extraction procedures provides a platform to investigate the activity of different forms and mixtures of Aβ species, and offers a tractable system to identify strategies to mitigate Aβ mediated neuritotoxicity.